Frequency of patients' consulting in general practice and workload generated by frequent attenders: comparisons between practices. - Neal, R D (1998)
BACKGROUND: Patients who attend frequently may present a problem for general practitioners (GPs) in several ways. The frequency of patients' consulting, comparisons between practices, and the effect of frequent consulting on the clinical workload have not been quantified previously. AIMS: To examine the distribution of the number of consultations per patient in four general practices. To estimate the clinical workload generated by frequent attenders. To model the data to demonstrate the contribution of age, sex, and practice on the likelihood of attending frequently. METHOD: Analysis and modelling of a validated data set of date records of consultations collected routinely over a 41-month period from four practices in and around Leeds, representing 44,146 patients and 470,712 consultations. RESULTS: A minority of patients consulted with extreme frequency. All practices had similar distributions but varied with respect to the numbers of frequent attenders, and the frequencies of their consulting. The most frequent 1% of attenders accounted for 6% of all consultations, and the most frequent 3% for 15% of all consultations. Females and older people were more likely to be frequent attenders. CONCLUSION: Frequent attenders have an important effect on GPs clinical workload. Between one in six and one in seven consultations are with the top 3% of attenders. Further research is needed to explain the behaviour underpinning frequent attendance in order to identify appropriate management strategies; such strategies could have an important effect on clinical workload.